Optimization of Growth Conditions of Serratia marcescens for Prodigiosin Production - Shaba, A.M.; Oyeleke, S.B.; Ijah U.J.J.; Oyewole, O.A.; Adamu, B.B.; Okeke, K.S.; Baba, J.; Cletus C.I. (UMYU Journal of Microbiology Research)
This study examined the optimization of growth conditions of Serratia marcescens isolated from a loamy soil of the Federal University Technology Minna Nigeria, for prodigiosin production. The different optimized conditions examined were extraction solvents, incubation time, pH, temperature, carbon sources, organic nitrogen sources, inorganic nitrogen sources and agitation levels. The result reveals that methanol is an ideal solvent recording absorbance of 0.69nm, which is slightly followed by ethanol and acetone with absorbance of 0.4nm and 0.3nm respectively. The bacterium produced maximum level of pigment after 36 hours of incubation (22.20µg/L), although pigment production was observed from 12 hours of incubation onwards (7.40µg/L). The pigment production declined after 36 hours of incubation. The results also revealed that pigment production by S. marcescens was maximum at 25°C (25.10µg/L) followed by 30oC (22.50µg/L). The optimal production was obtained at pH 7 (25.00mg/ml) with dextrose as optimal source of carbon (22.40mg/ml). There was no pigment production at static condition but maximum pigment production was recorded at 150 rpm (22.50µg/L). All the inorganic nitrogen sources caused a reduced biomass production. Among the organic nitrogen sources tested, yeast extract supported maximum pigment (26.75µg/L) but peptone led to a decreased pigment production (9.15µg/L) compared to other organic sources. Addition of urea did not support pigment as well as biomass production. Statistical analysis shows significant differences (p<0.05) in prodigiosin productions with different substrates, temperature and agitation levels. The study revealed that the production of prodigiosin was significantly influenced by the extraction solvents, incubation time, pH, temperature, carbon sources, organic nitrogen sources, inorganic nitrogen sources and agitation levels.